2012
DOI: 10.1111/j.1532-950x.2012.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant Removal Rate from Infection after Tibial Plateau Leveling Osteotomy in Dogs

Abstract: Objective To determine implant removal rate associated with infection after tibial plateau leveling osteotomy (TPLO) in dogs and to report antimicrobial susceptibility patterns for isolates. Study Design Retrospective case series. Animals Dogs (n = 255; 282 TPLO). Methods Medical records (April 2006–April 2008) for dogs that had TPLO with ≥ 18 month follow‐up were reviewed. Dogs that had implant removal with confirmed bacterial isolation from the implant were studied. Cefazolin (22 mg/kg intravenously) was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
68
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 18 publications
12
68
2
Order By: Relevance
“…19 TPLO may have a higher infection rate than other clean orthopedic surgeries, with rates of 3-12.5% being reported. 4,19,[31][32][33] A variety of antimicrobial protocols was used in these studies although in most, treatment was not continued beyond 24 hours after surgery. 4,32,33 After the first 750 TPLO in a series of 1000 consecutive TPLO, Fitzpatrick decreased the duration of postoperative antimicrobial therapy from 14 days to 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 TPLO may have a higher infection rate than other clean orthopedic surgeries, with rates of 3-12.5% being reported. 4,19,[31][32][33] A variety of antimicrobial protocols was used in these studies although in most, treatment was not continued beyond 24 hours after surgery. 4,32,33 After the first 750 TPLO in a series of 1000 consecutive TPLO, Fitzpatrick decreased the duration of postoperative antimicrobial therapy from 14 days to 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…4,19,[31][32][33] A variety of antimicrobial protocols was used in these studies although in most, treatment was not continued beyond 24 hours after surgery. 4,32,33 After the first 750 TPLO in a series of 1000 consecutive TPLO, Fitzpatrick decreased the duration of postoperative antimicrobial therapy from 14 days to 24 hours. 19 Without the figures from that study, it is difficult to draw definitive conclusions but multivariate analysis suggested a positive effect of prolonged postoperative antimicrobial therapy on SSI rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, this concern deserves attention when selecting surgical options. The infection rate following EAI was 2/59 (3.4 per cent) stifles,10 which compares favourably with reported TPLO implant removal rates resulting from surgical site infection of 325–7.4 per cent 26. While plate removal following bone healing is considered a good option following TPLO complicated by surgical site infection,27 28 plate removal before complete bone healing is potentially catastrophic for the limb.…”
Section: Discussionmentioning
confidence: 62%